ANALISIS PREFERENSI PENGGUNA TERHADAP HARGA DAN KEMUDAHAN PENGGUNAAN DALAM BERTRANSAKSI PRODUK KECANTIKAN PADA APLIKASI SHOPEE - Aprilia, Ervin; Fitria, Fitria; Aini, Qurra Aitul; Murdila, Murdila; Abrori, Rian (ITB Swadharma, 2024)
This research aims to understand Shopee app users' preferences regarding price and ease of use of the app in determining purchasing decisions for beauty products. The research method used is descriptive quantitative, utilizing primary data through the distribution of online questionnaires to 675 students from the Faculty of Economics and Business, class of 2022. From the total number of students, there were 125 respondents, and only 54 respondents met the sample criteria. The research results show that respondents' preferences for the Price variable yielded a